The effect of auditor switching, audit opinions, and financial distress on audit delay - Wicaksono, Yudho; Afrizal, Reza; Nunes, Arsenio Sinoc Almeida; Hidayat, Ihsan Dzuhur (Universitas Sebelas Maret, 2023)
Mining companies are among the Indonesian capital market's most popular or sought-after sectors. As companies listed on the Indonesia Stock Exchange (Bursa Efek Indonesia-BEI), they are also obliged to provide regular financial reports. An independent auditor will review this financial report. The process of auditing financial statements until the final report by an independent auditor is called audit delay. Audit delay is the time required to carry out an audit from the end of the financial year until an independent auditor completes the audit report. Researchers in this study looked at the possibility that audit delays were caused by factors such as auditor switching, audit opinion, and financial distress. Mining business actors on the Indonesia Stock Exchange (Bursa Efek Indonesia-BEI) are the subjects of this research. This research used non-probability sampling and purposive sampling to obtain 140 research samples. Non-participant observation is used to get this data. To analyze the data using multiple linear regression with the help of the Statistical Package for Social Science (SPSS) software. The research results show that auditor switching has no impact on audit delay. In the case of audit delay, it does not matter whether the auditor changes or not. On the other hand, audit delay can occur due to the audit opinion given by the auditor, especially if the argument is unreasonable. Last, audit delays are exacerbated if the company experiences financial distress, whether caused by internal or external factors. The reason is that when auditors carry out audits on companies experiencing financial distress, they will be more careful, and of course, it will take a long time.